The effects of pro-, pre-, and synbiotics supplementation on polycystic ovary syndrome: an umbrella review of meta-analyses of randomized controlled trials - Talebi, Sepide; Zeraattalab-Motlagh, Sheida; Jalilpiran, Yahya; Payandeh, Nastaran; Ansari, Shakila; Mohammadi, Hamed; Djafarian, Kurosh; Ranjbar, Mahsa; Sadeghi, Sara; Taghizadeh, Mahdiyeh; Shab-Bidar, Sakineh (Frontiers in Nutrition, 2023)
Background: Synbiotics, refer to a combination of probiotics and prebiotics in a form of synergism that beneficially affect the host's health by alternating the composition and/or function of the gut microbiota. Numerous meta-analyses of randomized clinical trials have proven that pro, pre-, and synbiotics supplementation has health outcomes in women with polycystic ovary syndrome (PCOS). However, the strength and quality of this evidence in aggregate have not yet been synthesized in great detail. Methods: PubMed, Scopus, Web of Sciences, and Google Scholar were searched up to March 2023. We pooled the mean difference and its 95% confidence interval (CI) by applying a random-effects model. Results: Overall, nine meta-analyses including a total of 12 trials were identified. The results of the present study indicated that probiotic supplementation significantly reduced the homeostatic model assessment for insulin resistance (HOMA-IR) (WMD: -0.29, 95% CI: -0.57 to -0.02, P=0.03, n=4; moderate certainty) and fasting glucose concentration (FGC) (WMD: -7.5 mg/dl, 95% CI: -13.60 to -0.51, P = 0.03; n=4; low certainty). Moreover, synbiotic supplementation had beneficial effects on glycemic control, lipid profile, and hormonal parameters, but the certainty of the evidence was rated as low to very low. However, supplementation with pro-/synbiotics did not affect inflammation and oxidative stress in women with PCOS. Furthermore, waist/hip circumference, fasting glucose concentration, lipid profile, dehydroepiandrosterone sulfate, high-sensitivity C-reactive protein, and hirsutism score were significantly reduced after prebiotics supplementation with low certainty of evidence. Conclusions: Although pro-, pre- and synbiotics supplementation had beneficial effects on some PCOS-related outcomes, the certainty of the evidence was rated as low to very low. Therefore, further well-designed RCTs might help to confirm our findings in women with PCOS.